University graduates’ work course during the economic crisis in Greece: the case of Philosophy and Social Studies graduates - Λιοδάκη, Νεκταρία (Ariadne, 2021)
THIS piece of research deals with our graduates at the Department of Philosophy and Social Studies, University of Crete. We observe their work course in the Greek labour market during the economic crisis. They have graduated between 2012 and 2016 and, 2 to 6 years after graduation they were asked about their work experiences. In the past, University of Crete Humanities seniors had replied to us (for a piece of research of ours) that they were optimistic about finding employment in their subject, despite the high unemployment rates. They were also confident about their social capital. Later, in another research of ours, teachers who worked in shadow education in Greece during the economic crisis, eloquently described the labour market mechanisms through which their work and payment conditions deteriorated significantly during that crisis. For this piece of research, we now focus on our department (Philosophy and Social Studies) graduates. We have sought feedback from them about their employment after graduation. We aim at examining their work experiences, not only out of interest in our former students, but also as an attempt to display the utilization of their studies in the labour market.